Impact of thermal processing on dietary flavonoids. (December 2022) - Gao, Yuan; Xia, Wei; Shao, Ping; Wu, Weijie; Chen, Hangjun; Fang, Xiangjun; Mu, Honglei; Xiao, Jianbo; Gao, Haiyan
Abstract : Flavonoids are widely distributed in natural products and foods as a class of polyphenols. They processed diverse bioactivities, including anti-inflammation activity, antiaging activity, and antioxidant activity. The foods rich in flavonoids are usually consumed after thermal processing. However, flavonoids are commonly vulnerable under thermal processing, and it could cause various influences on their stability and bioactivities. Therefore, in this review, the effects of thermal processing on thermal stability and bioactivities of dietary flavonoids from different food sources were first summarized. The strategies to improve thermal stability of dietary flavonoids were then discussed. Noticeably, the effect of some of the promising thermal technologies on dietary flavonoids was also clarified preliminarily in the current review. The promising thermal technologies may be an alternative to conventional thermal processing technologies. Graphical Abstract: Strategies to improve thermal stability of dietary flavonoids. ga1